Intellectual Genealogy of Tuan Guru H.M Said Amin Bima (1936-2015) - Muhammad Mutawali; Rahmah Murtadha; Ahmad Khoirul Fata (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2019)
The study on the Ulama in the Eastern Part of Indonesia, especially Bima and its surrounding area was scarcely limited, especially related to the Ulama Network in Nusantara during the XVIII-XX centuries. This study is expected to not only contribute to this lack of knowledge about the subject but also to pave a way for sustainable study on the network of Ulama from Bima in Nusantara. This paper will investigate one of the Ulama or Tuan Guru who lived in the XX century, which was the last generation of Ulama from Bima’s involvement in the Ulama Network of Nusantara, called Tuan Guru H. M. Said Amin. This study is focused on the intellectuality chain hence, its correlation with the Ulama Network of Nusantara can be found and this paper is concluded with several of his thoughts in Islamic law.